Hubungan Motivasi Ekstrinsik dalam Mendorong Prestasi Belajar Peserta Didik - Zahra, Wanda Aisyah; M, Marsofiyati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Motivation is seen as the spirit and internal drive that encourages a person to achieve certain goals. Motivation as one of the factors that can affect the improvement of students' learning achievement. This study aims to analyze the relationship of extrinsic motivation in encouraging students' learning achievement. This type of research is a qualitative literature review by critically evaluating the results of previous literature research. The data used is secondary data obtained from various references to previous research journals. The results in this study suggest that extrinsic motivation is able to encourage students to achieve individual learning achievements. Due to various influencing factors such as the environment, support from parents, teachers, and peers.